The Probable, Possible, and Novel Functions of ERp29 - Brecker, Margaret; Khakhina, Svetlana; Schubert, Tyler J.; Thompson, Zachary; Rubenstein, Ronald C. (Frontiers in Physiology, 2020)
The luminal endoplasmic reticulum (ER) protein of 29 kilodaltons (ERp29) is a ubiquitously expressed cellular agent with multiple critical roles. ERp29 regulates the biosynthesis and trafficking of several transmembrane and secretory proteins, including the cystic fibrosis transmembrane conductance regulator (CFTR), the epithelial sodium channel (ENaC), thyroglobulin, connexin 43 hemichannels, and proinsulin. ERp29 is hypothesized to promote ER to cis-Golgi cargo protein transport via COP II machinery through its interactions with the KDEL receptor; this interaction may facilitate the loading of ERp29 clients into COP II vesicles. ERp29 also plays a role in ER stress (ERS) and the unfolded protein response (UPR) and is implicated in oncogenesis. Here, we review the vast array of ERp29’s clients, its role as an ER to Golgi escort protein, and further suggest ERp29 as a potential target for therapies related to diseases of protein misfolding and mistrafficking.